1970
DOI: 10.1039/c29700001357
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of mycophenolic acid

Abstract: Incorporation experiments with [7-I4C]-5, 7dihydroxyphthalide (11) , [7-l4C]-6-gerany1-5, 7-dihydroxyphthalide (IV) , [7-14C]-5, 7-dihydroxy-4-methylphthalide (V), and [7-14C]-7-hydroxy-5-methoxy-4-methylphthalide (VI) suggest that only C7-lC1-5, 7-dihydroxy-4-methylphthalide (V) acts as the principal precursor of mycophenolic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The first insights into MPA biosynthesis, which were gained more than four decades ago from culture feeding studies using synthetic radioactive isotope labeling precursors, revealed its skeleton is derived from 5-methylorsellinic acid (5-MOA) and farnesyl pyrophosphate (FPP), and > a putative oxidative cleavage of the sesquiterpene (C 15 ) side chain (1012). The C -methyl group at C6 and the O -methyl group at C5 were proposed to originate from S -adenosyl-L-methionine (SAM) (10, 13). However, the genetic and enzymological bases for MPA biosynthesis remained obscure until the recent independent discoveries of three analogous MPA biosynthetic gene clusters ( SI Appendix , Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The first insights into MPA biosynthesis, which were gained more than four decades ago from culture feeding studies using synthetic radioactive isotope labeling precursors, revealed its skeleton is derived from 5-methylorsellinic acid (5-MOA) and farnesyl pyrophosphate (FPP), and > a putative oxidative cleavage of the sesquiterpene (C 15 ) side chain (1012). The C -methyl group at C6 and the O -methyl group at C5 were proposed to originate from S -adenosyl-L-methionine (SAM) (10, 13). However, the genetic and enzymological bases for MPA biosynthesis remained obscure until the recent independent discoveries of three analogous MPA biosynthetic gene clusters ( SI Appendix , Fig.…”
Section: Main Textmentioning
confidence: 99%
“…As biosynthetic evidence which indicates that C‐alkylation occurred preferentially in compounds having the m ‐dihydroxybenzene structure . Several attempts were made to introduce the side chain with the hydroxy ester 52 or with geraniol, or with trans , trans ‐ farnesol in the presence of p TsA or in an aqueous solution of acetic acid, or using ZnCl 2 and BF 3 etherate as catalyst on 63 failed.…”
Section: Reports Of the Total Synthesis Of Mycophenolic Acidmentioning
confidence: 99%
“…Penicillic acid (49) M e w o ~O P. aurantiogriseum, P. vanbeymae, P. expansum, P. fennelliae, P. griseofulvum, P. madriti, P. puberulum, P. roquefortii, P. simplicissimum, P. thomii, P. viridicatum (P. M. Scott, 1977) (also Birkinshaw and GowHand, 1962;01ivigni and BuHerman, 1978;Mosbach, 1960) OH CH z Me Ac HOV Botryodiplodin (50) P. hirsutum (Fujimoto et at., 1980), P. roquefortii (Renauld et at., 1984) 6-Farnesyl-5, 7 -dihydroxy-4-methylphthalide (51) P. brevicompactum (Canonica et at., 1971) Mycochromenic acid (54) P. brevicompactum (Campbell et at., 1966;Bird and Campbell, 1982b;Colombo et aI., 1982) For mycophenolic acid, also: P. paxilli , P. roqueJortii (Lafont et at., 1979), P. otivicotor (Oxford and Raistrick, 1933) 3,7-Dimethyl-8-hydroxy-6-methoxy isochroman (61) P. citrinum (Cox et at., 1979) Canescin (62) P. canescens R) = H, R2 = H: Scott, 1977); P. viridicatum (P. M. Scott, 1977;Damoglou et al, 1984); P. purpurescens, P. roquefortii, P. spinulosum (Leistner and Pitt, 1977); P.janthinellum (Czech patent, 1982) Me P. viridicatum (Hutchison et al, 1971) 1 R = H: Ochratoxin A (72) P. viridicatum (van Walbeek et ai., 1969;van cler Merwe et al, 1965;Damoglou et al, 1984); P. aurantiogriseum, P. purpurescens, P. variabile, P.…”
Section: Coohmentioning
confidence: 99%